Reduced placental volume and flow in severe growth restricted fetuses (Clinics, 2016)
OBJECTIVES: To evaluate placental volume and vascular indices in pregnancies with severe fetal growth restriction and determine their correlations to normal reference ranges and Doppler velocimetry results of uterine and umbilical arteries. METHODS: Twenty-seven fetuses with estimated weights below the 3rd percentile for gestational age were evaluated. Placental volume and vascular indices, including vascularization, flow, and vascularization flow indices, were measured by three-dimensional ultrasound using a rotational technique and compared to a previously described nomogram. The observed-to-expected placental volume ratio for gestational age and observed-to-expected placental volume ratio for fetal weight were calculated. Placental parameters correlated with the Doppler velocimetry results of uterine and umbilical arteries. RESULTS: The mean uterine artery pulsatility index was negatively correlated with the observed-to-expected placental volume ratio for gestational age, vascularization index and vascularization flow index. The observed-to-expected placental volume ratio for gestational age and observed-to-expected placental volume ratio for fetal weight and vascularization index were significantly lower in the group with a bilateral protodiastolic notch. No placental parameter correlated with the umbilical artery pulsatility index. CONCLUSIONS: Pregnancies complicated by severe fetal growth restriction are associated with reduced placental volume and vascularization. These findings are related to changes in uterine artery Doppler velocimetry. Future studies on managing severe fetal growth restriction should focus on combined results of placental three-dimensional ultrasound and Doppler studies of uterine arteries.